2023
DOI: 10.3390/ijms24097844
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Cancer Effects of Artesunate in Human 3D Tumor Models of Different Complexity

Abstract: The anti-malaria drug Artesunate (ART) shows strong anti-cancer effects in vitro; however, it shows only marginal treatment results in clinical cancer studies. In this study, ART was tested in preclinical 3D cancer models of increasing complexity using clinically relevant peak plasma concentrations to obtain further information for translation into clinical use. ART reduced cell viability in HCT-116 and HT-29 derived cancer spheroids (p < 0.001). HCT-116 spheroids responded dose-dependently, while HT-29 sph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 73 publications
0
1
0
Order By: Relevance
“…Artesunate (Art) is a semisynthetic sesquiterpene lactone compound that has been widely used as a first-line drug for malaria treatment. Compared with chemical drugs, Art as a derivative of artemisinin has relatively lower side effects and better pharmacokinetics. In addition to malaria treatment, Art has been also demonstrated to display antitumor effect possibly by inducing oxidative damage, cell cycle arrest, as well as signaling pathway disruption. Mounting evidence has shown that the peroxide-bridge (R–OO–R′) structure inside Art exerted a crucial role in the therapeutic effects. Specifically, the peroxide-bridge can react with ferrous ions via Fenton reaction to produce carbon-center radicals or reactive oxygen species (ROS), thereby resulting in irreversible oxidative damage to tumor cells. Given this feature, Art was considered as a potential CDT candidate for tumor therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Artesunate (Art) is a semisynthetic sesquiterpene lactone compound that has been widely used as a first-line drug for malaria treatment. Compared with chemical drugs, Art as a derivative of artemisinin has relatively lower side effects and better pharmacokinetics. In addition to malaria treatment, Art has been also demonstrated to display antitumor effect possibly by inducing oxidative damage, cell cycle arrest, as well as signaling pathway disruption. Mounting evidence has shown that the peroxide-bridge (R–OO–R′) structure inside Art exerted a crucial role in the therapeutic effects. Specifically, the peroxide-bridge can react with ferrous ions via Fenton reaction to produce carbon-center radicals or reactive oxygen species (ROS), thereby resulting in irreversible oxidative damage to tumor cells. Given this feature, Art was considered as a potential CDT candidate for tumor therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Artesunate is a water solubility derivative of artemisinin and the most effective drug for the treatment of severe malaria [ 13 ]. In recent years, its anti-tumor effects were explored as well [ 14 , 15 ]. Thus, introducing the artesunate group to metformin moiety may improve its anti-bladder cancer activity.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, introducing the artesunate group to metformin moiety may improve its anti-bladder cancer activity. Along with this thought, we [ 15 ] designed and obtained a new artesunate dimer triazine derivative AM2 by esterification of artesunate and metformin.…”
Section: Introductionmentioning
confidence: 99%
“…Heme present in the food vacuole of plasmodium interacts with the endoperoxide bridge of ART and activates it. The generation of reactive oxygen species subsequently binds to membrane protein and induces lipid peroxidation and, ultimately lysis of the plasmodium parasite [9]. Short half-life and rapid metabolism; however, limit the application of ART.…”
Section: Introductionmentioning
confidence: 99%